Student Responsibilities Towards Online Learning in Interactive Multimedia Courses - Dewi, Utari; Sumarno, Alim; Dimas, Hirnanda; Kristanto, Andi (Journal of Education Technology, 2022)
In online learning, an attitude of responsibility is needed in the learning process. Today, the attitude of responsibility in students is reduced. This study aims to look at the student's responsible attitude towards online learning in the interactive multimedia development course. This research is descriptive, namely research to describe the symptoms, phenomena, or facts studied by describing the independent variables, without intending to connect or compare. Data collection techniques using a Google Form questionnaire. The population in this study were students who were taking Interactive Multimedia courses totaling 167 respondents. The data obtained were analyzed using a descriptive percentage technique. The results of this study indicate that a very good attitude of responsibility in online interactive multimedia learning is related to aspects of punctuality in collecting assignments and knowing the lecture schedule, aspects of revising work and doing all assignments independently, aspects of using original ideas, and do not do plagiarism works. While the attitude of responsibility that is still lacking in online interactive multimedia learning is related to aspects of participation in online class forum discussions and providing suggestions or input on the work of colleagues, aspects of using illustrations/drawings themselves. So that we get the results that there are aspects of the attitude of responsibility related to social responsibility that is still lacking, while individual responsibility is quite good.